The case of the rainy day mystery - Preller, James; Smith, Jamie C.; Alley, R. W. (Robert W.) (New York : Scholastic, 2003)
Jigsaw is out to discover why tough Bigs is acting so oddly, reading babysitter club books and sneaking around.
"A Little Apple paperback."
RL 2.
006-009.
370
Accelerated Reader AR
Keywords: Schools -- Juvenile fiction; Mystery fiction